(untitled) (DAPesquisa, 2021)
Online education has emerged today as an alternative to formal education. Through digital information and communication technologies, one can study using different devices about tools, techniques and software, which has become even more popular in the area of Design. In this context, the aim of this study is to conduct a quantitative conceptual analysis of a database of 603 Graphic Design courses of Udemy platform, which offers online courses in various subjects. A general description of the courses, their levels and other variables are approached from descriptive statistics. As a result, there was a predominance of tool-related courses and courses for all levels or beginners. From the quantitative analysis, reflections on Design Education and Design Research as previously established are drawn, facing a possible new educational paradigm that has gained relevance in recent years: that of non-formal education.